A Majoritarian View of 'Gender Justice' in Contemporary India: Examining Media Coverage of 'Triple Talaq' and 'Love Jihad'. Issue 4 (4th July 2021) - Piedalue, Amy; Gilbertson, Amanda; Raturi, Manas
Abstract: This paper explores media coverage of instant 'triple talaq'—a form of divorce practised by some Indian Muslims—and 'love jihad'—a supposed trend of Muslim men coercing Hindu women into conversion and marriage. The Hindu Right position itself as champions of gender justice in the context of outlawing instant triple talaq, but in discussions of 'love jihad' sideline women's rights (to choose their own religion and spouse) and focus on national security. This reveals the strategic use of women's rights by the Hindu Right to further entrench its imagination of a secular Hindu nation threatened by the Muslim man.